A metapragmatic study of perceptions of politeness in peninsular spanish speakers of two generations - Hidalgo Downing, Raquel (Círculo de Lingüística Aplicada a la Comunicación, 2025)
Politeness studies in Spanish have a solid and rich tradition, with important contributions to the theoretical aspects of politeness with specific proposals for the Hispanic cultures as well as to the description of politeness in Spanish varieties, on which the bibliography is abundant (Iglesias Recuero, 2001). Since Blum-Kulka’s (1992) influential study on the metapragmatics of politeness in Israeli Hebrew and Eelin’s (2001) critical view of politeness theoretical models, however, the possibility of studying politeness not only in its linguistic formulations (the so-called second-order politeness) but also in the speakers’ evaluations of politeness (first order politeness) is set forward. This work is part of this trend, where studies in Spanish are scarce. Specifically, the present study aims to investigate the notion of lay politeness (Ogiermann y García- Conejos Blitvich, 2019) in an inter-generational study, that is, how two different generations approach their perceptions and conceptualizations of politeness in everyday life in today’s Spanish society. The study is based on the study of perceptions in young university students (18-21 years) and older university students (65-80 years) and aims to establish the similarities and differences in the way in which speakers perceive the role of politeness in daily life from an intergenerational approach, examining the metalanguage of politeness in such informants, associations and meanings of the terms under analysis
Keywords: Spanih pragmatsics; politeness; first order politeness; metapragmatsics; emic perceptions